Measurement of Uranium and Thorium Series in Fertilizer Samples in Iraq Using Gamma Spectrometry Technique - Murtadha Shakir Aswood; Murtadha Shakir Aswood (Al-Qadisiyah Journal of Pure Science, 2018)
The present work deals with identifying and determining the concentration of natural occurring radionuclides, 238U and 232Th series in fertilizers used in Iraq. A total of 20 samples collected from markets and farms. The gamma-ray spectrometer (HPGe) detector was used for measuring gamma ray spectra. The ranges of radioactivity levels of 214Pb, 214Bi, 212Pb, 208Tl and 228Ac are 402.53 – 17.09, 343.11– 2.50, 151.50 – 1.26, 67.62 – 1.12 and 42.84 – 3.53 Bqkg-1, respectively. The mean activities of 238U and 232Th series in fertilizers are 69.39 and 14.31 Bqkg-1 respectively. The obtained data are compared with available reported data from other countries in literature. The concentrations of 238U series and 232Th series in fertilizer are lower than the limit adopted in UNSCEAR (2000) reports, and within the limits of those used worldwide.